2018
DOI: 10.1007/s13738-018-1381-4
|View full text |Cite
|
Sign up to set email alerts
|

A mild and efficient H2O2 oxygenation of N-heteroaromatic compounds to the amine N-oxides and KI deoxygenation back to the tertiary amine with hexaphenyloxodiphosphonium triflate

Abstract: A mild and efficient H2O2 oxygenation of Nheteroaromatic compounds to the amine N-oxides and KI deoxygenation back to the tertiary amine with hexaphenyloxodiphosphonium triflate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As mild Lewis bases, pyridine N-oxides can result in activating Lewis acid parts of molecules and also increasing the reactivity of nucleophilic part toward different reactions with electrophiles. [115][116][117][118] Pyridines have been highly significant in catalyzing reactions, as reported in a study by Yoshida and coworkers. In this regard, they reported that when TBDPSCl, DIPEA, and pyrrolidinopyridine N-oxide (PPYO) catalyst are combined, it would bring about silylating different secondary alcohols in CH 2 Cl 2 at r.t. with excellent yields.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 82%
“…As mild Lewis bases, pyridine N-oxides can result in activating Lewis acid parts of molecules and also increasing the reactivity of nucleophilic part toward different reactions with electrophiles. [115][116][117][118] Pyridines have been highly significant in catalyzing reactions, as reported in a study by Yoshida and coworkers. In this regard, they reported that when TBDPSCl, DIPEA, and pyrrolidinopyridine N-oxide (PPYO) catalyst are combined, it would bring about silylating different secondary alcohols in CH 2 Cl 2 at r.t. with excellent yields.…”
Section: N-oxides Catalyzed the Silylation Of Hydroxyl Groupsmentioning
confidence: 82%